Application of x-means alghorithm for district/city clustering based on povetry rate in Maluku Islands and Papua - Matdoan, M. Y.; Igo, La (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2023)
Based on the Central Statistics Agency in 2022, the percentage and number of poor people according to islands in March 2022 explained that the largest number of poor people are on Maluku Island and Papua, 19.89 percent. This research used data mining techniques with the X-Means Clustering method. The data in this study was taken from the website of the Central Statistics Agency (BPS) of Maluku, North Maluku, Papua, and West Papua consisting of 63 regencies/cities with 8 variables. Then all the data was processed with Rapidminner and produced 3 clusters, namely cluster 0 consisting of Buru, Western Seram, Central Halmahera, Sula Islands, South Halmahera, North Halmahera, East Halmahera, Morotai Island, Jayapura, Nabire, Biak Numfor, Paniai, Pucak Jaya, Mimika, Tolikra, Nduga, Puncak and Manokwari. Cluster 1 consists of Tanimbar Islands, Southeast Maluku, Aru Islands, Eastern Seram, Southwest Maluku, South Buru, Tual, West Halmahera, Taliabu Island, Ternate, Tidore Islands, Yapen Islands, Boven Digoel, Mappi, Asmat, Star Mountains, Sarmi, Keerom, Waropen, Supiori, Mamberamo Jaya, Central Mamberamo, Yalimo, Dogiyai, Intan Jaya, Deiyai, Fakfak, Kaimana, Wondama Bay, Bentuni Bay, South Sorong, Sorong, Raja Ampat, Tambrauw, Maybrat, South Manokwari and Arfak Mountains and cluster 2 consisting of Central Maluku, Ambon, Merauke, Jayawijaya, Yahukimo, Lanny Jaya, Jayapura City, and Sorong City.